Annotated record of the detailed examination of Mn deposits dredged in the area of the Erben and Fieberling Guyots in the Eastern Pacific Ocean off San Diego - A J Carsola; Robert S Dietz (PANGAEA, 1952)
Erben and Fieberling Guyots lie about 800 and 600 miles, respectively, west of San Diego, California. Their tops are largely rocky. The sparse deposits consist of a thin patchy veneer of calcareous and siliceous organic remains and small amounts of clastic mineral grains and basalt fragments derived from the underlying rocks. The rocks of Erben Guyot are encrusted with manganese dioxide. Geomorphic and petrologic evidence indicate the seamounts to be extinct basaltic volcanoes. The drowned summit platforms of Erben Guyot (400 fathoms) and Fieberling Guyot (280 fathoms) are considered to be planes of marine abrasion cut by wave action within a few fathoms of sea level. Possible explanations are discussed for the present deeply drowned position of these truncated surfaces. It is concluded that these extinct submarine volcanoes constitute an uncompensated load on the earth extquotesingles crust of such magnitude that they tend to subside slowly because of yielding of the earth extquotesingles crust. Foraminifera of Miocene age have been identified in the calcareous cement of a breccia from the Erben Guyot surface. Thus, this guyot appears to have been truncated in Miocene or earlier time.
Supplement to: Carsola, AJ; Dietz, RS (1952): Submarine geology of two flat-topped northeast Pacific seamounts. American Journal of Science, 250(7), 481-497, https://doi.org/10.2475/ajs.250.7.481